Similar anatomical distributions of childhood naevi and cutaneous melanoma in young adults residing in northern and southern Sweden. Issue 14 (September 2015) - Karlsson, Maria A.; Rodvall, Ylva; Wahlgren, Carl-Fredrik; Wiklund, Kerstin; Lindelöf, Bernt
Abstract Background Common melanocytic naevi are considered early biomarkers associated with risk of cutaneous malignant melanoma. We sought to investigate if residing at different latitudes in Sweden influences the population's anatomical distribution of naevi in children and melanoma in adults. Methods The nationwide Swedish Cancer Registry 1990–2012 gave cumulative number of invasive melanomas per body site, stratified by sex and age in northern (62–69 °N) (n = 2823) and southern (55–58 °N) Sweden (n = 24, 115). A population-based cross-sectional study conducted in 2002 provided the allocation of naevi among 7-year-olds in northern (5695 naevi in 679 children) and southern Sweden (8392 naevi in 681 children). Results In 2012, northern Sweden had a two-fold lower melanoma incidence: 19.8/100.000 age-standardised population compared with 41.0/100.000 in the south. Similarly, a lower mean naevi density in children was demonstrated: 7.3 (standard deviation (SD) 5.4) in boys and 7.0 (4.7) in girls in the north versus 13.3 (8.4) in boys and 11.9 (8.5) in girls in the south. Across latitudes of residing, gender profiles and proportional body-site distributions of melanoma and naevi, respectively, were largely homogenous, but in southern Sweden slightly higher on the trunk; a body site associated with intermittent sun exposure. Childhood naevi distributions matched with melanomas in young and middle-aged adults. Conclusion This large population-based study demonstrated that latitude of residing similarly affects the number and anatomical distribution of naevi in children and melanoma in adults. It supports a role of childhood naevi as predictors of overall and subsite risk of melanoma among young adults.